Application of photocatalytic and fenton processes for the degradation of toxic pollutants from pulp and paper industry effluents - Mohammad Saleh Shafeeyan (Water Resources and Industry)
Pulp and paper mill effluents represent a significant environmental concern due to the presence of various toxic organic and inorganic pollutants, posing risks even at low concentrations. With the paper production process consuming approximately 200 tons of water per ton of paper and generating effluents containing over 250 different chemicals, effective treatment methods are essential to mitigate the environmental impact of the pulp and paper (PP) industry. This study presents a comprehensive evaluation of the efficacy of heterogeneous and homogeneous photocatalytic treatments for PP industry-derived effluents, targeting reductions in major pollutant concentrations below environmental standards. A thorough review of the literature on pollutant removal from PP effluents using photocatalytic treatment, particularly employing UV/TiO2 and UV/ZnO photocatalysts, reveals significant removal rates. Doped photocatalysts have shown enhanced performance, achieving removal percentages of 98 % for BOD and COD, and 99 % for color and lignin. Additionally, Fenton and photo-Fenton treatment techniques have demonstrated high removal efficiencies for BOD, COD, color, and lignin.